The clinical profile of internet addiction via a serie of 10 patients - Odabaşıoğlu, Gürkan; Öztürk, Özgür; Genç, Yasin; Pektaş, Özkan (Journal of Dependence, 2007)
Internet addiction has been a frequent psychopathology all over the world which psychiatrists dealing with addiction become to be familiar. On-line games and other pleasurable activities via internet may result with addiction probably using the same neurobiologic mechanisms which psycoactive substances also share. It is well known that especially chidren and adolescents are under risk for this disorder. Because of sociocultural factors, there is an important young population who are under severe risk in our country. In some of the cases with internet addiction, there are some comorbid psychiatric disorders which social phobia, attention deficit hyperactivity disorder and depression are most prominent. Some patients may have family history for pathologic gambling and substance abuse and addiction. Clinician must be aware of these comorbid situations for differtial diagnosis and appropriate treatment options. In this article, we present 10 child and adolescent cases who have applied to our clinic with complaints of excessive internet usage and aim to increase the clinicians’ awareness on the subject.
Keywords: Internet addiction; Addiction in child and adolescents; internet